Penggunaan Mediasi Dalam Penyelesaian Sengketa Tanah Gusuran Di Kantor Pertanahan Kota Serang - Santy Fitnawati WN; Asep Dharmawan; Rahmawati Rahmawati; Wahyu Rivaldi (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Land has a very important role in showing the independence and sovereignty of its owner, so that land disputes arise. But not all problems need to be resolved in court or trial. Currently there is a method of Alternative Dispute Resolution or ADR (alternative dispute resolution) which is a type of non-litigation dispute resolution which has recently become increasingly popular because it is implemented through mediation, where there is no bias from the mediator. The formulation of the problem in this research is that there are two main questions asked, first, the role of the land office in resolving land disputes through agreements and second, the Land Office making agreements in land disputes. The results of this research show that a mediator's responsibilities during mediation include facilitating discussions, enforcing the law, getting all parties to discuss problems and concerns honestly, helping each other remind each other that disputes are not battles that must be won but resolved, listening attentively, taking notes, and ask questions, and help all parties reach consensus or common ground. The procedure for resolving land disputes through mediation is by the disputing parties submitting a complaint to the Land Office, followed by a review, final negotiations and an agreement process. If all parties reach an agreement, the agreement is made in writing, whereas if an agreement is not reached, the parties have the option to take the case to court.